Gambaran Proses Klaim Covid–19 Orang dengan Gangguan Jiwa Ke Kementerian Kesehatan di RSJ Soeharto Heerdjan Tahun 2020-2021 - Annisa Bella Dyna (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2023)
In the beginning of 2020, the world is shocked with the outbreak of a new virus that is a new strain of Coronavirus (SARS-CoV-2) the disease itself is called Coronavirus disease 2019 (COVID-19). COVID-19 is infectious disease caused by Severe Acute Respiratory Syndrome Coronavirus 2. This disease spread throughout the world including Indonesia. COVID-19 could infect anyone including mentally ill people, because of high infection rate in Indonesia it become an emerging disease where the payment is done by government so the funds can be claimed in Ministry of Health, the claim could be done by referenced hospital that provide service for emerging disease patient including dr.Soeharto Heerdjan Mental Hospital. The aim for this research is to look for the process of COVID-19 claim for mentally ill people to Ministry of Health in dr.Soeharto Heerdjan Mental Hospital. The research method is descriptive qualitative. Data collection gained from interview and observation. Research result data suggest that dr.Soeharto Heerdjan Mental Hospital hasn’t own SPO for Covid-19 claim so that implementation process refers to Ministry of Health’s decision. Covid-19 claim process in dr.Soeharto Heerdjan Mental Hospital started when the patient has obtained  inpatient hospitalization, then the status is verified by verificator doctor, then the files is sent to casemix for completion verification of the files until  it’s submitted to BPJS and the Ministry of Health. The obstacle for Covid-19 claim process for mentally ill people in dr.Soeharto Heerdjan Mental Hospital among others are incomplete medical resume fulfillment, and disorder of e-claim system. Better to make detailed SPO regarding Covid-19 claim to Ministry of Health. It's advised to evaluate and review doctors to complete medical resume, and give warnings to doctors that still write incomplete medical resume.